High-temperature reliability of sintered microporous Ag on electroplated Ag, Au, and sputtered Ag metallization substrates - Chen, Chuantong; Suganuma, Katsuaki; Iwashige, Tomohito; Sugiura, Kazuhiko; Tsuruta, Kazuhiro (Journal of materials science. Materials in electronics, 2018)
Ag sinter joining technology has been used in the advanced power applications to replace conventional soldering technology due to its high temperature stability, along with its excellent electrical and thermal conductivity. In this paper, we report the high-temperature reliability (250 °C for 1000 h) for die-attachment structures using Ag sintering technology on Cu substrates with different top metallization layers (Au and Ag), formed via different deposition processes (electroplating and sputtering). The bonding strength over 40 MPa and high-temperature reliability of sintered Ag on the sputtered Ag surface was the best among the systems studied here. Bonding quality and the bonding fracture behavior of sintered Ag on the different metallization substrates were characterized. Ag–Au solid solution was formed due to metallizaion Au atoms diffused into sintered Ag layer, leading to decreased shear strength under high temperature process. The influence of grain structure on the bonding quality at the interface between sintered Ag and the metallization Ag layers were discussed. It revealed that the grain size and orientation of the top metallization Ag layer influenced the bonding quality. The sintered Ag layer formed by Ag hybrid particles may have a selective orientation of metallization layer on the surface (111) of the Ag crystal. These results will be helpful to understand both technological perspectives for design and the applications of sintered Ag from the viewpoint of high-temperature reliability, as well as the fundamental understanding of its bonding quality mechanism with top metallization layers.